Mutual Fund Expense Disclosures: A Behavioral Perspective - James D. Cox; John W. Payne (Washington University Law Quarterly, 2005)
The last few years have not been kind to the mutual fund industry. To be sure, financial indices have improved with the collateral benefit of boosting investor optimism so that the net gain in assets under management by registered investment companies rose by more than ten percent in 2004 to reach $8.6 trillion at the end of the year. But the mutual fund scandals that were first unearthed in fall 2003, with the accusations of late trading involving the Canary Fund, have been compounded by further allegations of late trading involving other funds. These scandals have been joined by pervasive instances of fund advisors looking the other way as important clients were permitted to abuse fund prohibitions against rapid trading. Even the well-established practice of revenue sharing, whereby brokers are rewarded by funds for recommending the fund to their clients, are being reconsidered in the post-Enron era in light of rising concerns over pervasive conflicts of interest within the financial services industry. For example, revenue sharing is now regulated. The various mutual fund scandals have invited public and political focus on the rising level of fees and expenses levied upon funds by their advisors. Thus, 2004 found not only numerous government enforcement actions that resulted in significant financial settlements, but also a tectonic shift in the regulatory quilt that covers the mutual fund industry. Foremost among the regulatory developments for the mutual fund industry is the requirement of heightened transparency of how registered investment companies cast their proxies for their portfolio companies. Greater transparency regarding how funds vote complicates the life of the fund manager by placing the manager between the conflicting needs of gaining admission as one of the acceptable vendors of 401K plans for a portfolio company’s employees and confronting a shareholder-friendly proposal (e.g., separating the position of CEO and board chair) that is opposed by that portfolio company’s management. The SEC also adopted corporate governance changes that essentially compel most funds to raise the number of fund directors who are independent of the fund’s advisor to three-fourths (from the statutorily mandated level of forty percent). And, as will be discussed, in 2004 the SEC expanded the amount of information that funds must disclose regarding fees and other costs that are charged to the fund’s assets. This articles concludes that any reporting of expenses should be placed in a context that invites easy comparisons by investors. The proposal l is not that there should necessarily be more information disclosed to mutual fund investors, but that much more attention should be given to the cognitive processes investors can be expected to employ in their response to the disclosures that are made.
Keywords: Mutual funds; Administrative fees; Management; Securities disclosure laws; Conflicts of interest; Corporate governance; Disclosure (Securities law); Mutual fund industry; United States